If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16(4y + -5) = 8(7y + 5) Reorder the terms: 16(-5 + 4y) = 8(7y + 5) (-5 * 16 + 4y * 16) = 8(7y + 5) (-80 + 64y) = 8(7y + 5) Reorder the terms: -80 + 64y = 8(5 + 7y) -80 + 64y = (5 * 8 + 7y * 8) -80 + 64y = (40 + 56y) Solving -80 + 64y = 40 + 56y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-56y' to each side of the equation. -80 + 64y + -56y = 40 + 56y + -56y Combine like terms: 64y + -56y = 8y -80 + 8y = 40 + 56y + -56y Combine like terms: 56y + -56y = 0 -80 + 8y = 40 + 0 -80 + 8y = 40 Add '80' to each side of the equation. -80 + 80 + 8y = 40 + 80 Combine like terms: -80 + 80 = 0 0 + 8y = 40 + 80 8y = 40 + 80 Combine like terms: 40 + 80 = 120 8y = 120 Divide each side by '8'. y = 15 Simplifying y = 15
| 5x-7/3=xx | | 5x-7u/2=2u-; | | -2(x-3)(x+3)-18=0 | | 3(5w-2)-4(3w-5)=w | | 28-x+30-x+3x+x=40 | | -7+6.5(1+2.5s)=-16.5 | | (T+0.5)4=5 | | -6xy+6xy= | | X(2)=5(5) | | f(-2)=(4m-3)/(m-7) | | 2(x-5)=7-2x | | 3sinx-4cosx-2=0 | | .2(7-x)=4 | | 5-3x-(-4x+6)=-(8x+11)-(3x-10) | | 42.5/y=x | | 2=(3+x)+3(2) | | x^(-1/5)=(1/3) | | x^-1/5=1/3 | | 8x+41y+10=180 | | 2n/3=4 | | x-x+3x+x+30+28=40 | | 5h-7-3h=2(h-14) | | a^3-64= | | (2c+1)=(c-5) | | 4x^2+4y^2-16x+32y-20=0 | | (2c-1)=(c-5) | | 12y-18/2 | | 16x-3=68+13+4x | | 2x+4x+2x+1+5x-6=60 | | r/s=25 | | 9x+1=9(1)+2 | | (37b-8)-9(4b+4)=-2 |